PENGARUH REBUSAN DAUN SELEDRI UNTUK MENYEMBUHKAN HIPERTENSI - Windi Novia Ramadhani; Shinta Dewi Kasih Bratha (Ensiklopedia of Journal, 2025)
Background: Hypertension is an abnormal increase in blood pressure in the arteries continuously for more than one period. One non-pharmacological treatment used to reduce high blood pressure is celery. Celery (Apium Graviolens L) is one type of herbal therapy for treating hypertension. Objective: From several literature reviews, this is to determine the effect of celery leaves in curing hypertension. Method: This research design uses a literature review. National journal searches using the Google Scholar data base used for the last 10 years. The search was carried out from 27 September to 26 December 2023. Results: From the analysis of 15 journals, it shows that there is an effect of celery leaves on the incidence of hypertension, men and women can suffer from a history of hypertension, but can reduce these symptoms by finding out what sources of information The effect of celery leaves to cure hypertension. Conclusion: There is an effect of giving boiled celery water on reducing blood pressure, both systole and diastole, in hypertensive sufferers.Keywords: Celery; Hypertension; Healing; Decoction; Herbal